Gate-Free InGaAs/InP Single-Photon Detector Working at Up to 100 Mcount/s - Alberto Tosi; Carmelo Scarcella; Gianluca Boso; Fabio Acerbi (IEEE Photonics Journal, 2013)
Recently, there has been considerable effort to develop photon-counting detectors for the near-infrared wavelength range, but the main limitation is to have a practical detector with both high count rates and low noise. Here, we show a novel technique to operate InGaAs/InP single-photon avalanche diodes (SPADs) in a free-running equivalent mode at high count rate up to 100 Mcount/s. The photodetector is enabled with a 915-MHz sinusoidal gate signal that is kept unlocked with respect to the light stimulus, resulting in a free-running equivalent operation of the SPAD, with an afterpulsing probability below 0.3%, a photon detection efficiency value of 3% at 1550 nm, a temporal resolution of 150 ps, and a dark count rate below 2000 count/s. Such gate-free approach can be used to measure, at high count rate, signals in continuous wave or with slow time decays, where standard gated detectors would not be suitable.